2018
DOI: 10.1038/s41388-018-0151-1
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α drives chemokine factor pro-tumoral signaling pathways in acute myeloid leukemia

Abstract: Approximately 80% of patients diagnosed with acute myeloid leukemia (AML) die as a consequence of failure to eradicate the tumor from the bone marrow microenvironment. We have recently shown that stroma-derived interleukin-8 (IL-8) promotes AML growth and survival in the bone marrow in response to AML-derived macrophage migration inhibitory factor (MIF). In the present study we show that high constitutive expression of MIF in AML blasts in the bone marrow is hypoxia-driven and, through knockdown of MIF, HIF1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Further studies are needed to better understand the functional differences in these pathways between subjects with highly proliferative vs. nonproliferative T cells. For example, hypoxia signaling promotes a protumorigenic microenvironment for many cancers, including AML, and leads to therapeutic resistance (54,55). Changes in the expression of genes involved in this pathway suggest that patients with AML may have dysregulation in the tumor immune environment in addition to variation in T cell proliferation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to better understand the functional differences in these pathways between subjects with highly proliferative vs. nonproliferative T cells. For example, hypoxia signaling promotes a protumorigenic microenvironment for many cancers, including AML, and leads to therapeutic resistance (54,55). Changes in the expression of genes involved in this pathway suggest that patients with AML may have dysregulation in the tumor immune environment in addition to variation in T cell proliferation and function.…”
Section: Discussionmentioning
confidence: 99%
“…37 Hypoxia, a key factor of the microenvironment, was also reported to drive pro-tumoral signaling in AML via a HIF1α/MIF/IL8 pathway that is also thought to play a role in chronic lymphocytic leukemia survival. 38 Stroma has also been shown to sustain AML cell resistance to cytarabine via activation of the AXL receptor upon AML cell-dependent education of stroma to secrete GAS6 in vitro . 21 We now provide evidence that several microenvironment messages converge to enhance AXL expression and activation, which sustain pro-survival signals to selectively protect FLT3-ITD AML cells from quizartinib treatment in situ .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that HIF-1α induces the expression of macrophage migration factor (MIF) [97], with drives interleukin-8 (IL-8) production by the BM mesenchymal stromal cells (BM-MSC), thereby supporting AML cell survival and proliferation [98]. Recently, HIF-1α has been shown to directly induce the expression of IL-8 in AML cell lines and in primary AML blasts, which in turn supports survival and proliferation of AML cells [99].…”
Section: Gene Expression Regulation Mediated By Hifs To Sustain Amlmentioning
confidence: 99%